Implications of Bone-Only Metastases in Breast Cancer: Favorable Preference with Excellent Outcomes of Hormone Receptor Positive Breast Cancer - Lee, Su Jin; Park, Silvia; Ahn, Hee Kyung; Yi, Jun Ho; Cho, Eun Yoon; Sun, Jong Mu; Lee, Jeong Eon; Nam, Seok Jin; Yang, Jung-Hyun; Park, Yeon Hee; Ahn, Jin Seok; Im, Young-Hyuck (Cancer research and treatment, 2011)
The aim of the current study was to determine the incidence, clinical presentation, and treatment outcomes of "bone-only metastases" in patients with breast cancer and to analyze the impact of hormone receptor (HR) and human epidermal growth factor receptor 2 (HER2) status on prognosis. Between 1994 and 2007, of 968 patients with metastatic breast cancer who underwent palliative management at Samsung Medical Center, 565 (57%) relapsed with distant metastases. Of the 968, 146 (15%) had bone-only metastases during a median follow-up period of 75 months. Among the 146 patients with bone-only metastases, 122 (84%) were relapsed patients after curative surgery and 24 (26%) were initially metastatic cases. The median time from primary surgery to bone-only metastases of the 122 patients was 37 months (95% confidence interval [CI], 27 to 46 months). Bone-only metastases were more common in the HR-positive group than in the other subtypes (85% for HR+; 8.2% for HER2+; 6.8% for triple negative. Among all 146 patients, 75 (51%) were treated with hormone therapy. The median post-relapse progression-free survival was 15 months (95% CI, 13 to 17 months). The median overall survival was much longer in the HR+ patients than the HER2+ and triple negative breast cancer patients with marginal statistical significance (65 vs. 40 vs. 40 months, p=0.077). Breast cancer patients with "bone-only metastases" had excellent clinical outcomes. Further study is now warranted to reveal the underlying biology that regulates the behavior of this indolent tumor, as it should identify 'favorable tumor characteristics' in addition to 'favorable preferential metastatic site.'